Inbreeding in a Family Tree and in a Population - A.N. Volobuev (Journal of Genetic Engineering, 2020)
On the basis of Hardy – Weinberg’s law the problem of inbreeding in a family tree and a population was investigated. With use of an inbreeding factor are received the discrete equation for a family tree and differential equation for a population. The numerical solution of the differential equation for a population was found and analyzed at various values of the inbreeding factor. Migration of inbred population is investigated in view of natural selection. It was shown that velocity of migration falls with increase of the inbreeding factor. Interrelation of the recessive allele frequency at woman for a migrating population with inbreeding factor and standard parameter of selection was found.
Keywords: Hardy-Weinberg’s law